Thermodynamics, statistical thermodynamics, and kinetics - Engel, Thomas; Reid, Philip (Noida: Pearson, 2006)
Thermodynamics, Statistical Thermodynamics and Kinetics is a groundbreaking new text that explains core topics in depth with a focus on basic principles, applications and modern research. The authors hone in on key concepts and cover them thoroughly and in detail - as opposed to the general, encyclopedic approach competing textbooks take. Excessive math formalism is avoided to keep students focused on the most important concepts and to provide greater clarity.
Appendices A-C, 543-598p.; Index 599-607p.
Keywords: Kinetics; Statistical thermodynamics; Thermodynamics; Chemistry